2022
DOI: 10.1007/s10620-022-07484-x
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked Symptoms in Autoimmune Hepatitis Negatively Impact Many Facets of Life

Abstract: Background Significant reduction in quality of life among patients with autoimmune hepatitis (AIH) patients has been observed in several studies. While acute symptoms associated with AIH have been well described, little is known about the overall impact of living with AIH on patients’ quality of life. The aim of this qualitative descriptive study was to describe the impact of AIH and associated symptoms on quality of life from the perspectives of patients living with AIH. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…74 Fatigue, anxiety, depression, and a globally reduced quality of life are reported by the vast majority of patients with autoimmune hepatitis. [75][76][77] Depression seems to be partly associated with prolonged steroid use, but the frequency and degree of depression in autoimmune hepatitis suggest additional factors influencing the decreased quality of life. 78 Being cared for in a referral center and having a trustful doctor-patient relationship were recently shown to have a strong positive influence on the overall quality of life 79 -a clearly modifiable factor that should receive more attention and strongly argues for a structured care system allowing access to expert care for all patients with autoimmune hepatitis, as well as quality control measures of the care delivered.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…74 Fatigue, anxiety, depression, and a globally reduced quality of life are reported by the vast majority of patients with autoimmune hepatitis. [75][76][77] Depression seems to be partly associated with prolonged steroid use, but the frequency and degree of depression in autoimmune hepatitis suggest additional factors influencing the decreased quality of life. 78 Being cared for in a referral center and having a trustful doctor-patient relationship were recently shown to have a strong positive influence on the overall quality of life 79 -a clearly modifiable factor that should receive more attention and strongly argues for a structured care system allowing access to expert care for all patients with autoimmune hepatitis, as well as quality control measures of the care delivered.…”
Section: Quality Of Lifementioning
confidence: 99%
“…In addition, azathioprine increases the risk of hematologic malignancy and skin cancer 74. Fatigue, anxiety, depression, and a globally reduced quality of life are reported by the vast majority of patients with autoimmune hepatitis 757677. Depression seems to be partly associated with prolonged steroid use, but the frequency and degree of depression in autoimmune hepatitis suggest additional factors influencing the decreased quality of life 78.…”
Section: Quality Of Lifementioning
confidence: 99%
“…This matches with data from the current literature, where depressive syndrome occurred in 10.8% and was found to be five times more frequent in AIH patients compared to the general population [ 39 ]. In addition, several studies have shown that severe symptoms of depression and anxiety negatively impact the quality of life in AIH patients [ 39 , 40 , 41 ]. Therefore, detailed psychiatric assessment and complementary psychological treatment offer the chance to improve care and should therefore be offered to AIH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological symptoms including fatigue, memory impairment, and sleep disturbances have been reported in patients diagnosed with autoimmune hepatitis, Primary Biliary Cholangitis (PBC), and Primary Sclerosing Cholangitis (PSC) ( Dyson et al, 2015 ; Zenouzi et al, 2018 ; Jones et al, 2023 ). The underlying mechanism governing development of these symptoms is not fully understood, and treatment options are currently an area of unmet need.…”
Section: Liver-brain Axis In Clinical Diseasementioning
confidence: 99%